Matrix controlled structural phase transformations in embedded metallic nanoparticles. (May 2022) - Hung, Cain J.; Nayak, Sanjeev K.; Parent, Lucas R.; Hebert, Rainer J.; Pamir Alpay, S.
Abstract: Non-equilibrium synthesis and post-processing methods may result in unique and unexpected microstructures. In arc-melted and subsequently laser-glazed Al-0.5 at% Co alloys, we show via high-resolution transmission electron microscopy lattice-imaging that cobalt forms coherent face-centered cubic nanoprecipitates. Using first-principles methods and a common-neighbor analysis, we explain the reasons for this and then expand the model by introducing nanoprecipitates of 4th-row transition metals into aluminum and titanium supercells. Our results indicate that the lattice strain and the physio-chemical interactions across the matrix-particle interface play significant roles in the crystal structure of the precipitate. Our computations make surprising predictions; for example, a hexagonal close packed copper can be stabilized in a titanium matrix and cubic zinc can be formed in an aluminum matrix. Extrapolating from these findings, we hypothesize that new allotropic forms of transition metals can be accessed through non-equilibrium processing and careful design of lattice strains. Graphical abstract: Image, graphical abstract